Does Hand Grip Correlate with Muscle Mass and Fat Mass? - Ardha, Muchamad Arif Al; Dzulkifl, Dzulkifl; Kurniawan, Wahyu Dwi; Budijono, Agung Prijo; Putro, Andika Bayu; Priantoro, Bimo Bintang (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
Introduction: In daily routines, especially in heavy weight lifting activities, grip strength is important. This study aims to investigate grip strength with muscle mass and fat mass in the arms. Methods: Cross-sectional study with the subjects of this study were 45 students (15 females and 30 males) with male characteristics (age 19.8±0.83, height 168±6.10, weight 64.7±11.5, BMI 22.9±3.82) while in women (age 20±0.78, height 159.3±4.43, weight 57.3±11.6, BMI 22.6±4.33). Spearman correlation from SPSS version 26 with a significance level of P-value < 0.05. Finding: Based on the data, there was no significant correlation between grip strength and muscle ma and arm fat mass. Then the muscle mass of the right side with (P-value: 0.079, r: 0.265) and the left side (P-value: 0.059, r: 0.284), while the mass of fat on the right side (P-value: 0.090, r-value -0.256) and the mass of fat on the left (P-value: 0.180, r-value: -0.204). Conclusion: This study proves that there is no correlation between grip strength and muscle mass or arm fat mass.